2008
DOI: 10.4049/jimmunol.180.11.7565
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Cathelicidin Antimicrobial Peptide Prevents Invasive Group A Streptococcus Infection of the Skin

Abstract: Mast cells (MC) express cathelicidin antimicrobial peptides that act as broad-spectrum antibiotics and influence the immune defense of multiple epithelial surfaces. We hypothesized that MC help protect against skin infection through the expression of cathelicidin. The susceptibility of MC-deficient mice (Kit Wsh−/−) to invasive group A streptococcus (GAS) was compared with control mice. Following s.c. injection of GAS, MC-deficient mice had 30% larger skin lesions, 80% more lesional bacteria, and 30% more sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
105
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 57 publications
2
105
0
1
Order By: Relevance
“…In previously published mouse models of skin and soft tissue infection with GAS, the bacteria were inoculated s.c. into the backs (8,32,36), haunches (6), or flanks (1,5,7,38). Compared to such models, the s.c. inoculation into both hind footpads in the present study was a simple procedure, and the obtained data showed a narrow dispersion of reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…In previously published mouse models of skin and soft tissue infection with GAS, the bacteria were inoculated s.c. into the backs (8,32,36), haunches (6), or flanks (1,5,7,38). Compared to such models, the s.c. inoculation into both hind footpads in the present study was a simple procedure, and the obtained data showed a narrow dispersion of reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that MCs also can respond to other types of live streptococci. For example, MCs have been shown to inhibit the growth of Streptococcus pyogenes by forming extracellular traps (65), and it has also been demonstrated that MCs contribute to the defense toward invasive group A streptococci by secreting cathelicidin (10). Moreover, Streptococcus pneumoniae was previously shown to activate RBL-2H3 cells, a cell line with MC-like characteristics (4).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are reports showing that MCs contribute to antibacterial defense without any signs of phagocytic activity (17). It has also been demonstrated that MCs can kill bacteria by formation of extracellular traps (65) and that MCs may express antimicrobial peptides (10).…”
mentioning
confidence: 99%
“…Regarding our findings that LL-37 similarly induces its own degradation by initiating MC degranulation, evidence is growing that MC-mediated cleavage may play a dual role during the course of inflammation, i.e., as an instigating as well as a limiting process. According to a very recent publication by Di Nardo et al (48), murine MC produce and proteolytically process the precursor CAP-18. However, the major CAP-18-derived cleavage product IGE24, generated upon activation with IL-4, retained microbicidal activity in contrast to the peptides generated by human MC from LL-37.…”
Section: Discussionmentioning
confidence: 99%